PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN DIGITAL MARKETING TERHADAP LOYALITAS PELANGGAN: Studi pada Pelanggan Kedai Hj.S Jl. Kesumba Kota Malang - Sidi, Agus Purnomo (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This research is a kind of field research, case study on Kedai Hj.S Jl.Kesumba Malang Town customers that aims to know how the influence of product quality, service quality and digital marketing to customer loyalty. The data were taken directly from the respondents through a questionnaire survey with Likert scale by random sampling to as many as 80 respondents. The results of data analysis using SPSS 23 software shows that both product quality, service quality and digital marketing have a significant effect on customer loyalty. Thus, to increase customer loyalty, it is suggested that Hj.S management to improve the product quality, or at least maintain the product quality, speed up the service processing and increase the social media usage.